A Differential Protection Scheme Based on Improved DTW Algorithm for Distribution Networks With Highly-Penetrated Distributed Generation - Xiren Miao; Dan Zhao; Baoquan Lin; Hao Jiang; Jing Chen (IEEE Access, 2023)
Differential protection has been introduced into the distribution network to address the ineffectiveness of traditional protection due to the uncertainties of power flow caused by the access of multiple inverter-interfaced distributed generation (IIDG). Designed for lower data synchronization costs, this paper proposes a novel differential protection scheme based on improved dynamic time warping (DTW) distance. The proposed algorithm can effectively alleviate the singularity caused by DTW’s excessive X-axis distortion through relaxation search and derivative estimation and minimize the impact of data synchronization errors and data loss. Based on the proposed algorithm, the protection scheme combined with the feeder terminal unit (FTU) for fast fault isolation is designed, which can make full use of the existing equipment and reduce costs. Moreover, multiple influencing factors considered in this scheme, including transition resistance, penetration rate, and output intermittency of IIDG, variable network topology, underground cables, and hybrid lines. The test results demonstrate that the proposed protection scheme can effectively isolate short-circuit faults in various scenarios.